Untangling Goal Tensions in Family Firms: A Sensemaking Approach - Diaz‐Moriana, Vanessa; Clinton, Eric; Kammerlander, Nadine (Journal of Management Studies, 2024)
AbstractWhile economic and non‐economic goals may converge in the long term, they often lead to tensions for organizational decision‐makers in the short term, especially in family firms that place much emphasis on family‐related goals. We draw on a sensemaking approach to investigate such potential tensions in the decision‐making of family firms. Based on a qualitative analysis of 59 interviews, 501 items of archival data and 39 observations from eight private Irish firms, we explore the perceived goal tensions of family firm decision‐makers as they seek to balance economic and non‐economic goals. We identify three sensemaking mechanisms – ensuring continuity in the family firm, preserving family cohesion, and delegating responsibilities to trusted advisors – that assist family firm decision‐makers in managing these goal tensions. Moreover, we identify that sensegiving based on three different values – sense of commitment, community embeddedness, and family firm identity – helps family firm decision‐makers to justify and communicate their decisions. Our model contributes to a more granular understanding of the management of goal tensions and of decision‐making in family firms by going beyond the question of whether family firms prioritize economic or non‐economic; instead, it reveals concrete processes showing how firms balance and aim to incorporate both goals. Furthermore, we advance knowledge on sensemaking in family firms by revealing how sensemaking can explain idiosyncratic family firm behaviour and by showing how family firm decision‐makers use specific values when ‘giving sense’ to justify their decisions.